The Influence of Consumer Trust and Service Quality on Purchase Decisions on the Shopee E-Commerce Application - Dahe, Zalma; Rehatta, Geradin; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2024)
This study examines the influence of consumer trust and service quality on purchase decisions in the context of the Shopee e-commerce application. The research employs a quantitative analysis method by surveying Shopee e-commerce application users to collect data through questionnaires. The consumer trust variables evaluated include trust in transaction security, product reliability, and Shopee's reputation. Meanwhile, the service quality variables involve responsiveness, delivery reliability, ease of application use, and product quality. The study results indicate that consumer trust and service quality significantly impact purchase decisions on the Shopee e-commerce application. Consumer trust in transaction security, product reliability, and Shopee's reputation positively influence purchase decisions.